2018
DOI: 10.1016/j.joco.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of post cataract surgery endophthalmitis in a tertiary referral center in Iran

Abstract: PurposeTo evaluate the treatment outcomes of patients with post cataract surgery endophthalmitis in our tertiary referral center.MethodsIn this prospective study, patients with presumed post cataract surgery endophthalmitis were treated based on the modified endophthalmitis vitrectomy study (EVS) guidelines and followed for at least three months. Visual and anatomical outcomes were assessed in the last follow-up visit.ResultsA total of 46 eyes with presumed post cataract surgery endophthalmitis were admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…14 reported a higher result of the improvement of final VA (20/40) reaching 51.8% after vitrectomy and intravitreal antibiotic injection. Other studies by Torabi et al 8 and Gower et al 18 reported final VA better than 6/60 after vitrectomy of 67.4% and 60%. This study shows the benefits of immediate vitrectomy to improve the final visual outcome even in cases with poor initial visual acuity.…”
Section: 13mentioning
confidence: 85%
See 1 more Smart Citation
“…14 reported a higher result of the improvement of final VA (20/40) reaching 51.8% after vitrectomy and intravitreal antibiotic injection. Other studies by Torabi et al 8 and Gower et al 18 reported final VA better than 6/60 after vitrectomy of 67.4% and 60%. This study shows the benefits of immediate vitrectomy to improve the final visual outcome even in cases with poor initial visual acuity.…”
Section: 13mentioning
confidence: 85%
“…3 The age range of post-cataract surgery endophthalmitis in this study was predominantly >60 years old (52.4%). Based on a study by Torabi et al 8 , it was found that the average age of postcataract surgery endophthalmitis patients were 68.7 years…”
Section: 12mentioning
confidence: 99%
“…The Endophthalmitis Vitrectomy Study indicated that Staphylococcus epidermidis was the most commonly isolated exogenous pathogen followed by Staphylococcus aureus , Streptococcus species, and Enterococcus species [ 33 ]. Other studies have also shown Staphylococcus epidermidis to be the most common pathogen [ 9 , 34 ] while Torabi et al [ 13 ] revealed that Streptococcus viridans was the most common pathogen. Kim et al [ 14 ] and Dave et al [ 15 ] reported that Pseudomonas aeruginosa was the most commonly isolated pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus species, and Enterococcus species [33]. Other studies have also shown Staphylococcus epidermidis to be the most common pathogen [9,34] while Torabi et al [13] revealed that Streptococcus viridans was the most common pathogen. Kim et al [14] and Dave et al [15] introduced, and the sources of detection included blood, urine, sputum, swimming pools, and water tanks.…”
Section: Journal Of Ophthalmologymentioning
confidence: 99%
See 1 more Smart Citation